Diffusion of hydrogen in rare gas solids: neutral H atoms and H+ protons - Beyer, M.; Niedner-Schatteburg, G.; Bondybey, V. E.; Savchenko, E. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
In this letter we review and compare the available information about the stability and spectroscopy of the hydrogen atoms and protons in rare-gas solids. Mechanism of the H+ duffusion involving protonated rare-gas dimer Rg2H+ formation in the lattice is discussed. We suggest that the puzzling differences in their behavior and the stability are due to the fact that diffusion of hydrogen atoms is thermally activated, while that of the protons is activated by vibrational excitation of the Rg2H+ under ambient temperature black body radiation.